Risiko und Chance das Jahrhunderthochwasser am Rhein 1882/1883 ; eine umweltgeschichtliche Betrachtung - Masius, Patrick (Universitätsverlag Göttingen, 2013)
Natural disasters are a challenge for human societies. The young German nation that reacted in the face of the 100-year Rhine flood (1882/83) can be characterized by the key elements of science, technology, economy, administration, and national consciousness. Given this framework the main actors used the disaster to expand their influence (e.g. scientific research) and to establish solidly relations. In sum, dealing with a natural disaster like the Rhine flood can only be understood in the opposing terms of risk and opportunity.